Complications of esophagectomies for cancer: Round table, XLVI Uruguayan Congress of Surgery - Henderson, Eduardo; Rodríguez, José L; Vivas, Carlos; Santandreu, Jorge; Olano, Estela; Segales, Estela; Biestro, Alberto; Sauvanet, Alain (Cirugía del Uruguay, 1998)
Our thanks in the first place to authorities of the XLVI Uruguayan Congress of Surgery by designating us to coordinate this Round Table and in particular to the Professors Luis Praderi and Oscar Balboa for their support and permanent advice. Esophageal cancer surgery is surgery difficult and is fraught with morbidity and mortality very important.